THE THERAPEUTIC EFFECTIVENESS OF KLOZAPHEN AND CLOSIVERON AT COW DICROCELIOSIS-STRONGYLOSIS INVASION - Kruchynenko, O. V.; Mykhailiutenko, S. M.; Klymenko, O. S. (Scientific Progress & Innovations, 2019)
Dicroceliosis and gastrointestinal strongylatoses are among the most widespread ruminant helminthoses in Ukraine and in the world. These cattle diseases are caused by trematodes of Dicrocoelium dendriticum and nematodes of the Strongylida line. Quite often, these helminthes parasitize in the form of mixed invasion, causing significant economic losses to farms. At present, there are a large number of publications on para-sites’ resistance to various groups of anti-helminthic preparations. The largest number of the former ones is devoted to helminthoses of the gastrointestinal tract. The article presents the results of studies as to deter-mining the species composition of gastrointestinal strongylata in cows at the state enterprise experimental farm “Chervonyi zemlerob”, as well as comparing the effectiveness of Clozaphen and Closiveron for dicro-celiosis-strogylosis invasion. Coproovoscopic studying and determining eggs in 1 g of feces were conducted by the method of V. N. Trach. In order to determine the species composition of strongylates, feces (50 g from each animal) were selected and subsequently cultured in a thermostat at the temperature of 27 0C for 10 days. According to the study results the animals on this farm were infested with nematodes of the Strongylida line: Haemonchus (Rudolphi, 1803), Bunostomum (Railliet, 1902), and Oesophagostomum (Rudolphi, 1803). Hemonchuses dominated (EI=80.0 %). To conduct the experiment, 2 experimental and 1 control groups of cows 3–8 years of age were formed at the state enterprise experimental farm “Chervonyi zemlerob”, which were given a single dose of Clozaphen and Closiveron preparations. Feces were selected for analysis on the 30th and 60th days after dehelminthization. Prior to the treatment of animals, it was found that all cows had eliminated eggs of gastrointestinal Strongylata and Dicrocelium dendriticum (prevalence = 100 %). Accord-ing to the results of the studies, the therapeutic effectiveness of Clozaphen and Closiveron for gastrointesti-nal strongylatoses was 100 % on the 30th day of the experiment, while it was 85.0 % and 90.0 % for dicroce-liosis, respectively. The intensive effectiveness of the preparations made 82.8 % and 87.6 %.